Tracheal Morphologic and Protein Alterations Following Short-Term Cigarette Mainstream Smoke Exposure to Rats - Carter, Charleata A. (Japanese Society of Toxicologic Pathology, 2012)
A short-term 5-day nose-only cigarette smoke exposure study was conducted in Fisher 344 rats to identify smoke-induced tracheal protein changes. Groups of 10 male and female 5 week old rats were assigned to 1 of 4 exposure groups. Animals received filtered air, or 75, 200 or 400 mg total particulate matter (TPM)/m(3) of diluted 3R4F Kentucky reference cigarette mainstream smoke. Exposures were conducted for 3 hrs/day, for 5 consecutive days. Tracheas from half the rats were processed for pathology, and tracheas from the other half of the rats frozen immediately for proteomics. We hypothesized that smoke will activate tracheal inflammatory, apoptotic, proliferative, and stress-induced pathways. Mucosal epithelial toxicity from the inhaled material was evidenced by cilia shortening and loss of tracheal mucosal epithelium in smoke-exposed animals. Mucosal thinning occurred in all smoke-exposed groups with hyperplastic reparative responses in the 200 and 400 mg TPM/m(3) groups. Tracheal lysates from control vs. treated animals were screened for 800 proteins using antibody-based microarray technology and subsequently the most changed proteins evaluated by Western blot. Tracheal proteins expressed at high levels that were markedly increased or decreased by smoke exposure depended on dose and gender and included caspase 5, ERK 1/2 and p38. Signaling pathways common between the morphologic and protein changes were stress, apoptosis, cell cycle control, cell proliferation and survival. Changes in identified proteins affected by smoke exposure were associated with tracheal mucosal pathology, may induce functional tracheal changes, and could serve as early indicators of tracheal damage and associated disease.